CLC (CENTERED LEARNING CIRCULAR): METODE REVITALISASI KEILMUAN EKONOMI ISLAM UNTUK KALANGAN MAHASISWA - Nur Fitroh Febrianto; Wahyuningsari Wahyuningsari (al-Uqud : Journal of Islamic Economics, 2017)
As the development of information and increasingly sophisticated technology this global era, not least the young generation, especially students who fall into the hedonism culture. Behavior hedonism related to squeezing economic life, so that the Indonesian people, especially students understand very well be an economic system that is set in the religion of the Islamic Economic system, need for us to understanding the implementation of religion in the economic field intensively. Improvements of social and economic poblem can be resolved through solutions offered by the Al-Quran and Al-Hadith. Laws and guidelines are clearly contained there in, but how the application of a person against the Islamic economic principles will depend in how they understand the rules. Therefore CLC emerge from the output of the Qur'an and Al-Hadith as the solution to social problems. Circular discussion-based learning with studying the phenomenon of the contemporary economy is expected to accelerate the economic understanding of Islam among non-economic students of Islam. CLC can also be interpreted mentoring. The method used is the analysis of FGD and fusion methods of comparative literature. The research results can be obtained, that turned out to be an average of CLC is a method of supporting the economic understanding of Islam for the students who are accelerated out of the classroom. Thus CLC (Centered Learning Circular) is a scientific method of economic revitalization of Islam for the students.